G322(P) Not bell's palsy anymore? lyme disease (ld) until proven otherwise. (12th March 2018) - Penrose, S; Walsh, H; Kumar, Y
Abstract : Aims: Lyme Borreliosis (LD) is becoming increasingly prevalent across parts of the UK. Recent evidence suggests that LD is the commonest cause of lower motor neuron type facial palsy (LMN FP) in children and adults in the USA. Historically, idiopathic LMN FP, termed Bell's palsy, was given as the commonest cause in the UK, we discuss whether current evidence suggests otherwise. Methods: We report 2 cases of LMN FP seen over an evening shift, which were subsequently serologically confirmed cases of LD. We also reviewed current literature and surveillance data. Results: LD is an infectious disease caused by the spirochaete Borrelia burgdorferi . It is the most common tick-borne infectious disease in the UK and is becoming increasingly prevalent in certain areas, affecting around 9.8/100 000, a figure that continues to rise. The presenting features are often non-specific in children, with Erythema Migrans being the commonest presenting feature which is often missed as a heralding sign. Two children presented with LMN FP who we treated empirically for LD with Amoxicillin with subsequent results confirming the diagnosis. One was a holiday maker from an area not reported to have Lyme disease and the second child was on holiday in Republic of Ireland with known prevalence of Lyme disease. Both children presented to medical services in the preceding days with a rash and one with unilateral facial swelling (with development of LMN FP on same side). It is thought that up to fifty percent of facial Palsy in Children may be as a result of LD. Conclusion: Our findings confirm that LD is increasingly more common in the UK and should be considered as the most common cause of LMN FP. Symptomatic LD is potentially progressive with long term consequences. We propose empiric treatment of all cases of LMN FP with Amoxicillin or Doxycycline whilst awaiting serological confirmation of LD. In addition, clinicians should be considering LD much earlier in the differential of children presenting with a LMN FP.